What does (low) education mean in terms of dementia risk? A systematic review and meta-analysis highlighting inconsistency in measuring and operationalising education. (December 2020) - Maccora, Janet; Peters, Ruth; Anstey, Kaarin J.
Abstract: Low education is considered an important modifiable risk factor for dementia worldwide, despite the lack of a formal consensus definition of low education. The primary aim of this systematic review was to document and address the inconsistency in measuring and operationalising education in dementia studies. A secondary aim was to consider the dose of education required to reduce dementia risk. The protocol was registered at PROSPERO with registration ID CRD42018096168. CINAHL, Cochrane, PsycInfo, and Pubmed databases were searched using terms related to education, dementia and/or MCI, and incidence. Studies were eligible for inclusion if a risk ratio for education and any dementia, Alzheimer's Disease (AD), Vascular Dementia (VaD) or Mild Cognitive Impairment (MCI) was reported in a population cognitively healthy at baseline. Sample sizes for 65 studies meeting selection criteria ranged from 152 to 12, 881, representing populations from 24 countries. Risk of bias, assessed using a tool designed specifically for dementia risk studies, was found to be medium or low for all studies. There were 23 continuous, 29 dichotomous, and 31 categorical operationalisations of education reported. Random effects meta-analyses from continuous operationalisations suggested each year of education reduced risk by eight percent for AD (95% CI:5–12%) and seven percent for any dementia (95% CI:6–9%). Dichotomous operationalisations indicated an increased risk for low education of 45% (95% CI:29–63%) for any dementia and 85% (95% CI:56–118%) for AD, however definitions of low education were heterogeneous, ranging from zero to 12 years. There were too few studies to produce summary ratios for VaD or MCI. We conclude that, while the evidence of an association between low education and dementia incidence is robust, inconsistency in the definition, measurement and operationalisation of education hinders the translation of this evidence into practical policy recommendations to reduce dementia risk.